Back to those walls: The women's memory of the Maze and Long Kesh prison in Northern Ireland. (April 2015) - Aguiar, Laura
The Prisons Memory Archive holds 23 filmed interviews of women who visited relatives or worked in the Maze and Long Kesh Prison during the Troubles in Northern Ireland. This article investigates what experiences are remembered when interviewees are brought back to a place of memory and whether such memories can challenge dominant views of women having a secondary role within the prison's history. I analyse the recordings of loyalist and republican relatives, an Open University Tutor and Probation Workers. My findings show that the materiality of the site stimulated the process of recalling and enabled participants to re-enact past experiences. They also reveal that the remembering process varied according to the level of traumatic experiences of each participant and that some places are associated with specific events. The findings also show that women played a key role not only within the prison walls but also in the wider conflict context.